Transformation of consumer behavior post-crisis: a qualitative mixed methods approach in food retail - Câmpian, Veronica; Stanca, Liana; Dabija, Dan-Cristian (Journal of Business Economics and Management, 2026)
Following successive global health, energy, and geopolitical shocks, this research investigates the persistent transformation of retail consumption patterns. While extant literature examines crisis-driven behavior, a methodological gap remains in synthesizing rich qualitative data with advanced computational techniques. This study addresses this gap by employing a mixed-methods design, integrating Principal Component Analysis (PCA) and Sentiment Analysis, to uncover the latent behavioral and affective dimensions of post-crisis decision-making. Conducted in 2024 within the Romanian emerging market, the study utilizes focus group data to identify core drivers of behavioral change. Results reveal an accelerated adoption of retail technologies, a fundamental recalibration of purchasing priorities, and heightened expectations regarding the shopping experience. Sentiment analysis highlights significant variance in consumer adaptation, offering a granular perspective on emotional responses to the “new normal.” Theoretically, this work contributes to interdisciplinary scholarship on economic uncertainty and digital transformation. Practically, the findings provide actionable intelligence for firms to develop engagement and innovation strategies that align with emerging consumer needs in volatile environments. By bridging structural patterns with emotional dynamics, the paper offers a robust framework for understanding consumer resilience in the wake of systemic disruptions.